Black phosphorus analogue tin sulfide nanosheets: synthesis and application as near-infrared photothermal agents and drug delivery platforms for cancer therapy. Issue 29 (26th June 2018) - Xie, Zhongjian; Wang, Dou; Fan, Taojian; Xing, Chenyang; Li, Zhongjun; Tao, Wei; Liu, Liping; Bao, Shiyun; Fan, Dianyuan; Zhang, Han
Abstract : Black phosphorus analogue tin sulfide nanosheets as photothermal and drug delivery agents with high drug loading capacity for cancer therapy. Abstract : Two-dimensional (2D) inorganic nanomaterials for biomedical applications still face the challenge of simultaneously offering a high photothermal conversion efficiency (PTCE), efficient drug delivery, biocompatibility and biodegradability. Herein, cancer treatment using tin sulfide nanosheet (SnS NS)-based dual therapy nano-platforms (SDTNPs), including photothermal- and chemo-therapy, is demonstrated. SnS, a black phosphorus (BP) analogue binary IV–VI compound, was synthesized using liquid phase exfoliation. SnS NSs comprising 2–4 layers exhibited good biocompatibility and a high PTCE of 39.3%, which is higher than other popular 2D materials. The SnS NSs showed a stable photothermal performance over 2 h of laser irradiation and exhibited ∼14% degradation after 10 h of irradiation. It was also found that SnS NSs show high loading of small molecules such as doxorubicin (DOX) (up to ∼200% in weight). Consequently, the SDTNPs achieved notable tumor therapy through the combination of photothermal- and chemo-therapy both in vitro and in vivo . Our study may pave the way for the biomedical application of SnS and other IV–VI compound-based 2D nanomaterials. Compared with traditional therapies, SnS NS-based laser therapy is green and efficient, due to its biocompatibility, photo-degradability, high efficiency photothermal properties and high drug loading.